Capital controls: a selective study on the Malaysian perspective / Muhamad Rafangai Bardi - Bardi, Muhamad Rafangai (Faculty of Business and Management, 2000)
Before we go any further with this topic, it is essential to state that this paper is part of the course requirements to finish up Bachelor in Finance 04. The purpose of this study is to see whether the implement of capital control in Malaysia is effectively or not. This project paper also finding the Malaysian experience with the use of capital controls. This paper provides a review of the experiences of Malaysia that used capital controls to overcome the currency crises that occurs in 1997-98. Before embarking on this review, general considerations involved in the use of capital controls are briefly summarized, with observations on the types and objectives of capital controls, the problems that arise in evaluating their effectiveness, and the potential costs that may be associated with their use. The paper will shed some light on arguments; on some of the operational issues related to the design of capital controls; and on the relationship between capital controls and prudential policies. Lastly, this project paper will provide some conclusions as well as some recommendations towards the using of this capital control in Malaysia.